2017
DOI: 10.1371/journal.pntd.0005785
|View full text |Cite
|
Sign up to set email alerts
|

An economic evaluation of vector control in the age of a dengue vaccine

Abstract: IntroductionDengue is a rapidly emerging vector-borne Neglected Tropical Disease, with a 30-fold increase in the number of cases reported since 1960. The economic cost of the illness is measured in the billions of dollars annually. Environmental change and unplanned urbanization are conspiring to raise the health and economic cost even further beyond the reach of health systems and households. The health-sector response has depended in large part on control of the Aedes aegypti and Ae. albopictus (mosquito) ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
77
0
5

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(82 citation statements)
references
References 68 publications
(68 reference statements)
0
77
0
5
Order By: Relevance
“…We applied results of our simulations to Stauch et al [43], WHO [44], Fitzpatrick et al [45], and Sevá et al [46] to suggest how explicit assessment of uncertainties associated with sand fly ecology might provide additional value to assessments of vector control needs. Each of these studies provided data which can be used to estimate the percent reduction in vector populations constituting efficacious control.…”
Section: Application Of Results To Other Studiesmentioning
confidence: 99%
“…We applied results of our simulations to Stauch et al [43], WHO [44], Fitzpatrick et al [45], and Sevá et al [46] to suggest how explicit assessment of uncertainties associated with sand fly ecology might provide additional value to assessments of vector control needs. Each of these studies provided data which can be used to estimate the percent reduction in vector populations constituting efficacious control.…”
Section: Application Of Results To Other Studiesmentioning
confidence: 99%
“…Vector control remains the most viable option thus far for dengue control and prevention [17], and understanding the seasonality of dengue is of great value for identifying the optimal timing for intense vector control. In Thailand, all vector control programmes (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that unfortunately no single vector control intervention may be enough to reach elimination of dengue and using multiple interventions which require behavior change may reduce individual intervention effectiveness. Some studies have suggested combining imperfect vector control with an imperfect medium-high efficacy vaccine could be more efficacious and cost-effective way to reduce dengue cases [47,48].…”
Section: Discussionmentioning
confidence: 99%